Replication of neurovirulent equine herpesvirus type 1 (EHV-1) in CD172a+ monocytic cells. (February 2017) - Laval, Kathlyn; Van Cleemput, Jolien; Poelaert, Katrien C.; Brown, Ivy K.; Nauwynck, Hans J.
Highlights: Neurovirulent EHV-1 restricts its replication in CD172a + cells. The replication of EHV-1 neurovirulent is not delayed and controlled by HDAC. Differential HDAC control in CD172a cells may reflect different EHV-1 pathogeneses. Abstract: Equine herpesvirus type 1 (EHV-1) is responsible for respiratory disorders, abortion and myeloencephalopathy (EHM) in horses. Two pathotypes of EHV-1 strains are circulating in the field: neurovirulent (N) and non-neurovirulent (NN). For both strains, CD172a + monocytic cells are one of the main carrier cells of EHV-1 during primary infection, allowing the virus to invade the horse's body. Recently, we showed that EHV-1 NN strains showed a restricted and delayed replication in CD172a + cells. Here we characterize the in vitro replication kinetics of two EHV-1 N strains in CD172a + cells and investigate if the replication of these strains is similarly silenced as shown for EHV-1 NN strains. We found that EHV-1 N replication was restricted to 7–8% in CD172a + cells compared to 100% in control RK-13 cells. EHV-1 N replication was not delayed in CD172a + cells but virus production was significant lower (10 3.0 TCID50 /10 5 inoculated cells) than in RK-13 cells (10 8.5 TCID50 /10 5 inoculated cells). Approximately 0.04% of CD172a + cells produced and transmitted infectious EHV-1 to neighbour cells compared to 65% of RK-13 cells. Unlike what we observed for the NN strain, pretreatment of CD172a + cells with histone deacetylases inhibitors (HDACi) did not influence the replication of EHV-1 N strains in these cells. Overall, these results show that the EHV-1 replication of N strains in CD172a + cells differs from that observed for NN strains, which may contribute to their different pathogeneses in vivo .